Multi-channel marketing, branding and retail design : new challenges and opportunities - McIntyre, Charles; Melewar, T. C.; Dennis, Charles (Bingley, UK : Emerald Group Publishing Limited, 2016)
This unique book focuses upon service design, including retail and multi-channel marketing matters pertinent to the current age where physical contact with consumers has resurfaced as an enduring part of the marketing and branding landscape - complementary to online and virtual worlds.
Part I. The design process: branding, marketing and customer experience in a multi-channel world -- Part II. Structural experience in retail design and brand marketing: real world and beyond.
Keywords: Marketing; Marketing channels; Retail trade; markkinointi; brändäys; vähittäiskauppa